Diversity and evolution of optically complex eyes in a family of deep-sea fish: Ocular diverticula in barreleye spookfish (Opisthoproctidae) - Wagner, Hans-Joachim; Genner, Martin J.; Partridge, Julian C.; Chung, Wen-Sung; Marshall, N. Justin; Robison, Bruce H.; Douglas, Ronald H. (Frontiers in Ecology and Evolution, 2022)
Several families of mesopelagic fish have tubular eyes that are usually upwardly directed. These maximise sensitivity to dim downwelling sunlight and dorsal bioluminescence, as well as facilitating the detection of dark silhouettes above the animal. Such eyes, however, have a much-reduced field of view and will not be sensitive to, for example, lateral and ventral bioluminescent stimuli. All mesopelagic Opisthoproctidae so far examined have evolved mechanisms for extending the limited visual field of their eyes using approximately ventrolaterally directed, light-sensitive, diverticula. Some genera have small rudimentary lateral retinal areas capable of detecting only unfocussed illumination. Others have more extensive structures resulting in eyes that simultaneously focus light from above onto the main retina of the tubular eye using a lens, while diverticula produce focussed images of ventrolateral illumination using either refraction or reflection. These bipartite structures represent perhaps the most optically complex of all vertebrate eyes. Here we extend the limited previous data on the ocular morphology of five Opisthoproctidae (Opisthoproctus soleatus, Winteria telescopa, Dolichopteryx longipes, Rhynchohyalus natalensis, Bathylychnops exilis) using a combination of histology and magnetic resonance imaging and provide a preliminary description of the eyes of Macropinna microstoma. We note an increase in diverticular complexity over the life span of some species and quantify the contribution of the diverticulum to the eye’s total neural output in D. longipes and R. natalensis (25% and 20% respectively). To help understand the evolution of Opisthoproctidae ocular diversity, a phylogeny, including all the species whose eye types are known, was reconstructed using DNA sequences from 15 mitochondrial and four nuclear genes. Mapping the different types of diverticula onto this phylogeny suggests a process of repeated evolution of complex ocular morphology from more rudimentary diverticula.